Online Customer Reviews and Price Discounts on Online Purchasing Decisions on The Shopee Marketplace - Rusniati Rusniati; Ahsanul Haq; Priyougie Priyougie (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Consumers can purchase products via the internet. This research aims to analyze the influence of online customer reviews and price discounts, both simultaneously and partially, on online purchasing decisions in the Shopee marketplace. This research is causality research. The population in this research is consumers in Indonesia who have made purchases through the Shopee Indonesia application. The sampling technique used was purposive sampling with a sample size of 100 people. Multiple regression analysis is used as a data analysis technique. The results showed that online customer reviews and price discounts simultaneously influence online purchasing decisions at the Shopee marketplace. Online customer reviews partially affect online purchasing decisions, and price discounts partially affect online purchasing decisions in the Shopee marketplace.